1999
DOI: 10.1074/jbc.274.34.23734
|View full text |Cite
|
Sign up to set email alerts
|

The Light Chain of Factor VIII Comprises a Binding Site for Low Density Lipoprotein Receptor-related Protein

Abstract: In the present study, the interaction between the endocytic receptor low density lipoprotein receptor-related protein (LRP) and coagulation factor VIII (FVIII) was investigated. Using purified components, FVIII was found to bind to LRP in a reversible and dose-dependent manner (K d Ϸ 60 nM). The interaction appeared to be specific because the LRP antagonist receptor-associated protein readily inhibited binding of FVIII to LRP (IC 50 ; K d Ϸ 50 nM). Furthermore, experiments using recombinant FVIII C2 domain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
258
2
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 201 publications
(280 citation statements)
references
References 47 publications
(40 reference statements)
18
258
2
2
Order By: Relevance
“…In a series of studies by Mertens and co-workers (2,64,65), it was shown that the CR clusters of LDLR and LRP compete for binding to FVIII. Within each of the LRP clusters II and IV, approximately four adjacent CRs form a binding site for FVIII (31,33), whereas the matching epitope of FVIII involves multiple lysines on all three domains of its light chain (65)(66)(67)(68). Consistent with this, the anti-FVIII ScFv KM33, which recognizes the C1-domain of the light chain, interferes with FVIII binding to both LDLR and LRP (46,48,69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of studies by Mertens and co-workers (2,64,65), it was shown that the CR clusters of LDLR and LRP compete for binding to FVIII. Within each of the LRP clusters II and IV, approximately four adjacent CRs form a binding site for FVIII (31,33), whereas the matching epitope of FVIII involves multiple lysines on all three domains of its light chain (65)(66)(67)(68). Consistent with this, the anti-FVIII ScFv KM33, which recognizes the C1-domain of the light chain, interferes with FVIII binding to both LDLR and LRP (46,48,69).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the FVIII-binding site in LDLR is unknown. In vitro, the affinity of FVIII to LDLR (K D of ϳ200 nM) (14) was found to be less than to LRP (K D of ϳ80 nM) (2,5,33). Such affinities are unlikely to provide effective direct interactions of FVIII with both receptors in vivo, considering the concentration of FVIII in plasma (ϳ0.3 nM).…”
Section: Factor VIII (Fviii)mentioning
confidence: 99%
“…Investigation of the molecular basis thereof has recently started. [11][12][13] It has been demonstrated that FVIII clearance is facilitated by cell surface heparan sulfate proteoglycans. 13 These are thought to act by preconcentrating ligands on the cell surface that subsequently transfer their ligands to endocytic receptors.…”
Section: Introductionmentioning
confidence: 99%
“…LRP can bind and internalize a diverse spectrum of structurally unrelated ligands in a calcium-dependent manner including apolipoproteins, lipases, proteinases, proteinase-inhibitor complexes, Kunitz-type inhibitors, matrix proteins, and other proteins such as lactoferrin, Pseudomonas exotoxin A, and malaria circumsporozoite protein (1,2). In addition, the blood coagulation factor VIII was recently identified as a ligand of LRP (3). The broad range of ligands suggests a role for the receptor in distinct physiological and pathophysiological processes, ranging from lipoprotein metabolism, cell growth and cell migration, fibrinolysis, and thrombosis to atherosclerosis and Alzheimer's disease.…”
mentioning
confidence: 99%